Information System Audit Of Voter Data Using The Deliver, Service, And Support Domain Of The COBIT 5 Framework (Case Study: XYZ District Electoral Commission) - Versanika, Dayanni Vera (RISTEC : Research in Information Systems and Technology, 2024)
The General Election Commission (KPU) of XYZ  Regency supports the existence of information systems and well-functioning IT within an organization, which can help achieve its goals and objectives. The Program and Data Subdivision at KPU XYZ  Regency is one of the subdivisions that implements an Information System using the Voter Data System (Sidalih) to enhance the utilization of IT and assist in realizing targets and achieving objectives related to data management and operational services. Sidalih requires an audit to evaluate, measure the level of capability, and provide recommendations that have not yet been assessed for the current system. The audit standard to be used is the Control Objectives for Information and Related Technology (COBIT) 5, which aligns with Sidalih as the information system is currently operational. The results obtained from the Voter Data Information System, referring to the Deliver, Service, and Support (DSS) domain, indicate a capability level of 2, which is Managed Process, while the target level to be achieved is 3, which is Established Process. This is based on a gap analysis that broadly indicates the need to improve the capability level from the existing condition, focusing on enhancing activities with recommendations to maximize what is already functioning well and to carry out activities aimed at achieving the objectives.